Analysis Study of the Water Quality of Siombak Lake Medan North Sumatera - Rahmadhani Fitri; Batumahadi Siregar; Wanapri Pangaribuan (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Siombak Lake was formed due to land excavation for the construction of the Belawan - Medan - Tanjung Morawa (BELMERA) toll road, which spans 34 km. Frequent tidal flooding in this lake threatens tourism activities and surrounding settlements, leading to changes in the lake's water environment quality. The water quality of Siombak Lake, as part of water spatial planning, is the subject of this study. Regulation of the Minister of Environment No. 115 of 2003 established the Storet method for this study. The results show that the water in Siombak Lake is brackish and experiences daily tidal fluctuations. The Belawan River, which flows into the Malacca Strait, influences the tides of Siombak Lake. Siombak Lake is an open water body affected by tides. It is saline and has high oxygen levels. The high phosphate levels indicate that these waters are already polluted.